2020
DOI: 10.1007/s13592-020-00744-7
|View full text |Cite
|
Sign up to set email alerts
|

Can introgression in M-lineage honey bees be detected by abdominal colour patterns?

Abstract: Honey bee abdominal pigmentation is one of the most recognisable traits and it is often used by beekeepers as an indicator of M-lineage subspecies purity. However, this approach may negatively impact population diversity and is futile if there is no association between tergite colour patterns and the genetic background. To assess whether this trait can be used as a proxy for introgression proportions in M-lineage subspecies, we genotyped, with highly informative SNP assays, A. m. mellifera and A. m. iberiensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our results on these simulated hybrids provided insights on the applicability of the 96 AIM panel and we found that it was effective to detect recent cases of admixture as long as (1) admixed samples identified as such are present in the training set, and (2) admixture is relatively recent. In our tests, the classification was perfect up to the 2nd generation when crossing with the M lineage and up to the 4th generation with the C lineage, a type of admixture that is more likely to occur [ 34 ]. Also of interest, the comparison of the selected GI1 list with all the variants (see Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results on these simulated hybrids provided insights on the applicability of the 96 AIM panel and we found that it was effective to detect recent cases of admixture as long as (1) admixed samples identified as such are present in the training set, and (2) admixture is relatively recent. In our tests, the classification was perfect up to the 2nd generation when crossing with the M lineage and up to the 4th generation with the C lineage, a type of admixture that is more likely to occur [ 34 ]. Also of interest, the comparison of the selected GI1 list with all the variants (see Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Coloration is assessed at the first, second, and third abdominal tergites. The degree of coloration is assessed using different scales [7,8,14,15] as described by Ruttner [2]. Coloration patterns are classified into groups based on the extent to which changes are observed.…”
Section: Introductionmentioning
confidence: 99%
“…For scientific purposes, ten-grade scales are used [4,5], which enables us to capture more natural variability. For use in breeding programs, a four-grade scale is commonly used [14,15]. The highest grade means no yellow marks in abdominal tergites, and the lowest grade marks yellow bands on the first, second, third, and sometimes even on the fourth abdominal tergite.…”
Section: Introductionmentioning
confidence: 99%